Increased recombinant adeno‐associated virus production by HEK293 cells using small molecule chemical additives. Issue 3 (22nd December 2022) - Scarrott, Joseph M.; Johari, Yusuf B.; Pohle, Thilo H.; Liu, Ping; Mayer, Ayda; James, David C.
Abstract: Recombinant adeno‐associated virus (rAAV) has established itself as a highly efficacious gene delivery vector with a well characterised safety profile allowing broad clinical application. Recent successes in rAAV‐mediated gene therapy clinical trials will continue to drive demand for improved rAAV production processes to reduce costs. Here, we demonstrate that small molecule bioactive chemical additives can significantly increase recombinant AAV vector production by human embryonic kidney (HEK) cells up to three‐fold. Nocodazole (an anti‐mitotic agent) and M344 (a selective histone deacetylase inhibitor) were identified as positive regulators of rAAV8 genome titre in a microplate screening assay. Addition of nocodazole to triple‐transfected HEK293 suspension cells producing rAAV arrested cells in G2/M phase, increased average cell volume and reduced viable cell density relative to untreated rAAV producing cells at harvest. Final crude genome vector titre from nocodazole treated cultures was >2‐fold higher compared to non‐treated cultures. Further investigation showed nocodazole addition to cultures to be time critical. Genome titre improvement was found to be scalable and serotype independent across two distinct rAAV serotypes, rAAV8 and rAAV9. Furthermore, a combination of M344 and nocodazole produced a positive additive effect on rAAV8 genome titre, resulting in a three‐fold increase in genome titre compared to untreated cells. Graphical Abstract and Lay Summary: Transient triple‐plasmid transfection‐based recombinant adeno‐associated virus (rAAV) production was carried out at microplate scale to allow for screening of multiple small molecule cell culture additives. Two chemicals (nocodazole and M344) were found to positively regulate rAAV genome titre when added to rAAV producing cell culture shortly after plasmid transfection. As a result, addition of 4 μM nocodazole and 2.5 μM M344 to rAAV‐producing cultures improved crude genomic titre by up to three‐fold when compared to untreated rAAV producing cultures.